Social Norms, Entrepreneurial Attitude, and Perceived Behavioral Control for Womens Entrepreneurial Intentions: A Moderated Mediation Model - Gautam, Prakash Kumar (Tribhuvan University Journal, 2026)
Developing entrepreneurship is key to economic sustainability; however, the determinants of entrepreneurial intention need to be uncovered, especially among females. This study aims to investigate the determinants of entrepreneurial intentions among female undergraduate students in Kathmandu. Using a deductive approach, survey-based primary data from 403 conveniently selected female students were analyzed using a Structural Equation Model to test whether social norms, attitude, and behavioral control variables determine entrepreneurial intentions. Results revealed an indirect effect of social norms through entrepreneurial attitude and perceived behavioral control, highlighting that supportive social environments enhance confidence and favorable perceptions toward entrepreneurship. Both entrepreneurial attitude and perceived behavioral control emerge as strong predictors of intention. Family profession was found to be a strong moderator, with stronger effects observed among students from non-business backgrounds. The findings extend the Theory of Planned Behavior and highlight the importance of social context, focused education, and family exposure in fostering women’s entrepreneurship.